Hubungan Perilaku Ibu dengan Pemberian Makanan Pendamping ASI (MP-ASI) pada Bayi Usia 6-24 Bulan di Puskesmas Bies Kabupaten AcehTengah Tahun 2022 - Juwita Kumala Sari Daeng; Nur Azizah; Adelina Sembiring; Gusni Syariah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Complementary Foods for Breast Milk (MP-ASI) are additional intake given to babies aged 6–24 months to meet nutritional needs other than breast milk. Giving MP-ASI that is not in accordance with the baby's age or condition can have a negative impact on the nutritional status and digestive system of the child. This study aims to determine the relationship between maternal behavior—which includes knowledge, attitudes, and actions—and the administration of MP-ASI in infants aged 6–24 months at the Bies Health Center, Central Aceh Regency, in 2022. The design of this study was quantitative with a cross-sectional approach, involving 35 respondents who were selected purposively. The results of the univariate analysis showed that most mothers had good knowledge (45.7%), positive attitudes (74.3%), and good actions (45.7%) in giving MP-ASI. Meanwhile, the provision of MP-ASI is also mostly in the good category (48.6%). The results of bivariate analysis with the chi-square test showed a significant relationship between knowledge (p=0.007), attitude (p=0.003), and maternal actions (p=0.001) with MP-ASI. In conclusion, maternal behavior has a significant relationship with MP-ASI feeding practices. Therefore, improving nutrition education and counseling is very important to encourage optimal maternal behavior in fulfilling child nutrition.